Analysis of choriocapillaris vascular density in patients with retinitis pigmentosa caused by RPGR gene mutations - Carlo Gesualdo; Settimio Rossi; Clemente Maria Iodice; Paolo Melillo; Ernesto Marano; Antonio Del Giudice; Mauro Di Martino; Francesco Testa; Francesca Simonelli (BMC Ophthalmology)
Abstract Background Anatomic features characterizing the onset and progression of Retinitis Pigmentosa (RP) are still not clear and increasing interest has grown towards the impaired retinal flow in such disease. However, to date there are still few and inconsistent data exploring the changes reflected in vascular plexuses during the disease course, in particular regarding Choriocapillaris (CC). Therefore, the purpose of this study aimed at evaluating the CC perfusion in a cohort of males with RPGR-related X-Linked RP (XLRP). Methods Best corrected visual acuity (BCVA), color fundus photograph, fundus autofluorescence (FAF), optical coherence tomography (OCT), OCT-angiography (OCTA) and microperimetry (MP) were performed in 13 XLRP patients (22 eyes) harboring mutations in RPGR. The percent perfused CC area (PPCA) was analyzed and correlated with the phenotypic variables and mutation location. Moreover, the PPCA of RPGR-related XLRP patients was compared with age-matched healthy controls. Results The PPCA of the cases was 25.4% ± 7.5%, while controls displayed a PPCA of 32.3% ± 6.1% (p < 0.002). Moreover, PPCA appeared to be not significantly correlated with any of the anatomical and functional parameters analyzed, nor with the age of the patients, the duration of the disease and with the genotype. Conclusions The PPCA resulted significantly reduced in patients with RPGR-related XLRP when compared to age-matched healthy controls.